Identifikasi Serangga yang Berasosiasi dengan Tanaman Jeruk Citrus sinensis L. di Agro Techno Centre (ATC) Universitas Sriwijaya - Oktaviani, Oktaviani (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Oktaviani, O. (2023). Identification of insects associated with orange plants Citrus sinensis L. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 464-471). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Orange plant Citrus sinensis L. is a fruit that is widely cultivated in the area of South Sumatra. Productivity of orange plants is still relatively low because of the many disturbances encountered. The main disturbance in orange plants today is a disruption in their cultivation practices. Pests of citrus plants can cause farmers difficulties in getting maximum results. Investigating the species of pest attacking orange plants is important to determine what steps to take. The aimed of the research was identified insect pests and attack symptoms in the orange plant C. sinensis at the Sriwijaya University Agrotech Training Center (ATC), Ogan Ilir, South Sumatra. Research is carried out by survey methods. Catching and observing insect pests was done once a week for ± 2 months. The results of the research state that pest insects obtained in the orange plant C. sinensis are Blattella vaga, Bothrogonia addita, Cletus punctiger, Diaphorina citri, Hypomeces squamosus, Leptoglossus gonagra, Nezara viridula, Planococcus citri, Rhynchocoris longirostris, and Toxoptera aurantii. The species that dominates pests in the orange plant C. sinensis is the Rhynchocoris longirostris. It can be concluded that the insect that is known to damage orange plants C. sinensis L. is the order of the hemiptera and the spiny green ladybug species R. longirostris. This ladybug saves the eggs in leaves with an amount of 9 to 14 eggs. Ladybug eggs will hatch for ± 5-8 days after being placed. The spent cycle consists of eggs, five instars, nymphs and adults.